Does anticholinergic burden influence therapeutic success in treatment naïve overactive bladder patients?
Abstract Introduction: Overactive bladder is a bothersome condition for which anticholinergic drugs (AC) are a cornerstone treatment. Nevertheless, many patients have comorbidities requiring treatment with drugs that, besides their main pharmacologic target, have also anticholinergic properties. Recently, growing concern has surrounded AC's adverse effects. Anticholinergic burden (ABu) represents the cumulative effect of taking one or more medications with anticholinergic action in an individual and is quantifiable by several validated scales, such as the Drug Burden Index (DBI). We aimed to describe ABu in treatment naïve OAB patients, analyze prescription trends according to ABu, and study its impact on OAB treatment success. Methods: We retrospectively reviewed all patients referred to our outpatient clinic for OAB in 2021 and 2022. Exclusion criteria included neurogenic bladder; patients who already started on AC/Mirabegron for OAB by the referring physician; history of pelvic radiotherapy; history of bladder cancer; postvoid residual volume > 200 mL; clinically significant stress urinary incontinence; chronic pelvic pain syndrome, congenital urinary tract malformations, history of bladder surgery, history of midurethral sling or prostatic surgery, chronic kidney failure on dialysis. ABu was ascertained using Drug Burden Index (DBI). The study was approved by our institution 's ethics committee. Results: During the study 's time frame, 102 treatment naïve OAB patients were referred to our outpatient clinic. Mean age was 62,36 ± 15,05 years and 82,4% of patients were women. OAB wet was the most frequent phenotype as 74,5% of patients reported urge incontinence, using a mean of 2,78 ± 1,56 pads per day (PPD).AC drugs were the initial treatment in 98% of cases. Median (range) DBI was 0,09 (0-3,07). AC drugs were the most frequently prescribed therapy across all DBI groups (0;0-1;>1). On follow up appointment, 61,5% of patients reported improvement of their complaints with the prescribed therapy. In the group of patients with a DBI of 0, 77,1% reported improving after AC therapy, in those with a DBI between 0 and 1, 52 % reported improving and in the group with a DBI>1 only 25,9% reported improving after AC therapy. DBI was significantly higher in the group of patients reporting no improvement after therapy when compared to those who reported improvement. This result was confirmed using a binary logistic regression model. Conclusion: Urologists are still not attentive of ABu when treating OAB, as AC drugs were the most prescribed medication irrespective of DBI. Patients with a higher ABu demonstrated worse treatment outcomes, confirming ABu is an important determinant of AC therapy success. Therefore, physicians may need to consider drugs targeting other pathways such as the beta 3 adrenergic receptor in this group of patients.